Unveiling an in-plane Hall effect in rutile RuO2 films - Meng Wang; Jianbing Zhang; Di Tian; Pu Yu; Fumitaka Kagawa (Communications Physics)
Abstract The in-plane-magnetic-field-induced Hall effect (IPHE) observed in Weyl semimetals and PT-symmetric antiferromagnets has attracted increasing attention, as it breaks the stereotype that the Hall effect is induced by an out-of-plane magnetic field or magnetization. To date, the IPHE has been discussed mainly for materials with low-symmetry crystal/magnetic point groups. Here, we show that even if symmetry forbids an inherent IPHE that arises from any mechanism, an apparent IPHE can be generated by selecting a low-symmetry crystalline plane for measurement. For rutile RuO2, although its high symmetry forbids an inherent IPHE, films grown along the low-symmetry (1 1 1) and (1 0 1) orientations are found to exhibit a distinct IPHE. The in-plane Hall coefficients are quantitatively reproduced by referring to the out-of-plane Hall coefficients measured for the high-symmetry (1 0 0) and (0 0 1) planes, indicating that the observed IPHE is caused by a superposition of inequivalent out-of-plane Hall effects. Similar behaviour is also observed for paramagnetic rutile systems, indicating the ubiquity of the apparent IPHE in electronic and spintronic devices with low-symmetry crystalline planes.